LOCAL LEGENDS: EFL MATERIALS DEVELOPMENT FOR INDONESIAN TEENAGE LEARNERS - Jonner Simarmata (Universitas Negeri Padang, 2016)
Recently, materials development has attained big attention from ELT practitioners. Teachers, materials writers, and even producers are now trying to create attractive materials because they think that attractive materials will bring about great success in EFL teaching. Tomlinson (2003) says that materials are anything (linguistic, visual, auditory, or kinesthetic) that facilitate learning of language. In Indonesia, the goal of studying English at schools is not only for developing communicative competence but also for building characters. One of the materials sources that can be used for both goals is literary work. However, when talking about literary work as EFL teaching materials, usually teachers and even commercial materials writers have tendency to use western works. Of course, I see no objection to this idea. However, local legends are also beneficial in EFL teaching especially when we correlate it with the two goals of EFL teaching to Indonesian teenage learners. In Indonesia, there are many legends. Usually, these legends are orally passed on from one generation to another. However, today many of them have been written in books. These legends, for sure, have values – educative or humanitarian – to be learned. As far as my concern, many legends have been used for language teaching materials especially for L1 classrooms. Only a few of them have been used for EFL classrooms. This paper discusses about how to use local legends as materials for EFL class in Indonesian context. Specifically, this paper will talk about a) the theoretical and practical reasons of why local legends are good for EFL materials, and b) teaching strategies that can be used to benefit from local legends for EFL students.